THE INFLUENCE OF PATIENT EXPERIENCE BASED ON PATIENT-REPORTED EXPERIENCE MEASURES (PREMS) ON PATIENT VISITS MEDIATED BY PATIENT SATISFACTION IN THE EMERGENCY DEPARTMENT OF RSHPD - Petricia; Hery Winoto TJ (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The stagnation of patient visits in the Emergency Department of RSHPD may be influenced by patient experience and satisfaction with healthcare services. This study aims to analyze the influence of patient experience based on Patient-Reported Experience Measures (PREMs) on patient visits mediated by patient satisfaction. A quantitative survey design is used involving 341 respondents who visit the emergency department from January to March 2026. Data are collected using an electronic questionnaire integrated with the Hospital Management Information System (SIMRS) and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results show that patient experience based on PREMs significantly influences patient visits and patient satisfaction. Patient satisfaction also has a significant positive effect on patient visits. Furthermore, patient satisfaction mediates the relationship between patient experience based on PREMs and patient visits. This study indicates that positive patient experience and higher patient satisfaction may increase patient visits to emergency department services. Therefore, hospitals should continuously improve service quality and patient-centered care to enhance patient experience and patient satisfaction.